Modified silicon-based negative electrode material, preparation method thereof and lithium ion battery
By applying fluorinated polymer on the surface of the silicon-based anode material of lithium-ion batteries and sintered to form a fluorinated interface layer, the problem of interface instability caused by volume expansion during the circulation of the silicon-based anode material is solved, and high cycle stability is achieved Combined with high energy density.
Patent Information
- Application Number
- CN202411322773.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2024-12-27
AI Technical Summary
The silicon-based anode material in lithium-ion batteries has unstable interface mechanical and electrochemical performance due to volume expansion during the charging-discharge cycle. The existing technical solutions cannot effectively solve it, resulting in rapid deterioration of electrical performance.
By applying fluorinated polymer to the surface of the silicon-based material and performing sintering treatment, a fluorinated interface layer with high mechanical strength, electronic insulation and interface energy is formed to buffer expansion stress and reduce interface side reactions.
The interface stability and cyclic performance of the silicon-based negative electrode material are significantly improved, and the high energy density is maintained, and the problems of surface cladding and energy density reduction in the prior art are avoided.
Smart Images

Figure CN119191300A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of battery materials, and in particular to a surface-modified silicon-based negative electrode material, a method for preparing the material, and a negative electrode and a lithium-ion battery manufactured using the material. Background Art
[0002] Lithium-ion batteries are widely used in various industrial and daily life applications due to their low cost, abundant raw materials, and high energy density. Consumers are also eager to further improve the specific capacity of existing lithium-ion batteries.
[0003] At present, the mainstream negative electrode material in lithium-ion batteries is graphite, but the main drawback of graphite negative electrode material is that its theoretical specific capacity is very low (372mAh·g -1 , LiC6), it is difficult to meet the development needs of high energy density lithium-ion batteries under the premise of using graphite as the negative electrode material. Compared with graphite, silicon-based negative electrode materials have a high specific capacity (3579mAh·g -1 , Li 3.75 Si) and low lithium insertion and extraction potential (~0.4V) make it an excellent candidate material to replace graphite negative electrode. However, with the development of silicon-based negative electrode materials, some new and serious problems have emerged that need to be overcome. For example, with the charge-discharge cycle of lithium-ion batteries, the lithium insertion and extraction process of silicon-based negative electrodes is accompanied by a huge volume expansion effect (~300%). This huge volume change will lead to high instability in the mechanical and electrochemical properties of the silicon negative electrode interface and repeated rupture and repair of the solid electrolyte interface film (SEI film), thereby making the electrical properties of lithium-ion batteries using silicon-based negative electrode materials themselves very unstable and rapidly deteriorating with the progress of the charge-discharge cycle.
[0004] In order to solve this problem, researchers have invested a lot of money and manpower in research and proposed many solutions to improve the interface stability of silicon-based negative electrode materials, such as surface coating, bulk doping, porosification, nano-ization, high-concentration electrolyte engineering, etc. However, these solutions reported in the prior art cannot really solve the problem effectively, but will bring some additional defects. For example, the solution reported in the prior art of applying a surface coating layer on the silicon-based negative electrode material will still cause the surface coating layer to break and fall off in the later stage of the cycle due to low mechanical strength and low elongation, and it is difficult to achieve a long-term protection effect; bulk doping mainly improves the internal ion / electron transmission pathway, and the surface SEI film is still under the pressure of high expansion stress, and the problem is not solved fundamentally; the porosification and nano-ization strategies reduce the damage of expansion stress, but its large specific surface area and low first efficiency reduce the most important advantage of high energy density of silicon-based negative electrode materials. This solution runs counter to the demand for high energy density in the field; the lithium salt concentration of the high-concentration electrolyte is high, the manufacturing cost is high, and the electrolyte viscosity is high, which is difficult to meet the demand for high charging rate. Therefore, to date, there is a lack of solutions in this field that can truly solve the above problems. Therefore, how to construct a structural / electrochemically stable silicon-based negative electrode interface to maximize the advantages of the energy density of the silicon-based negative electrode is a technical difficulty that needs to be urgently solved.
[0005] In order to solve the above problems, the inventors of the present invention have conducted a lot of in-depth research and developed a novel silicon-based negative electrode material whose surface is modified with fluorine. During the electrochemical cycle, the negative electrode material exhibits excellent properties of high mechanical strength, high electronic insulation and high interface energy, which can effectively buffer the damage of silicon negative electrode expansion stress and reduce interface side reactions, effectively solving the problems of the prior art. Summary of the invention
[0006] The first aspect of the present invention provides a method for preparing a surface fluorine-modified silicon-based negative electrode material, the method comprising the following steps:
[0007] Step 1: applying a fluorine-containing polymer on the surface of the silicon-based material;
[0008] Step 2: Sintering the silicon-based material with the fluorine-containing polymer applied on the surface to obtain the surface fluorine-modified silicon-based negative electrode material.
[0009] According to one embodiment of the first aspect of the present application, the fluorine-containing polymer is selected from one or more of the following: polyvinylidene fluoride, polytetrafluoroethylene, polyvinylidene fluoride-hexafluoropropylene, polychlorotrifluoroethylene, polyvinyl fluoride, and ethylene-chlorotrifluoroethylene copolymer.
[0010] According to another embodiment of the first aspect of the present application, the weight average molecular weight of the fluorine-containing polymer is 15,000 to 2,000,000.
[0011] According to another embodiment of the first aspect of the present application, in the step 1, the mass ratio of the silicon-based material to the fluorine-containing polymer is 100:0.5 to 100:6.
[0012] According to another embodiment of the first aspect of the present application, in step 1, a fluoropolymer is applied to the surface of the silicon-based material by mixing a liquid dispersion of the fluoropolymer with the silicon-based material and then drying the mixture. According to another preferred embodiment of the first aspect of the present application, the liquid dispersion contains a dispersion medium such as water, ethanol or N-methylpyrrolidone in addition to the fluoropolymer. According to another embodiment of the first aspect of the present application, the drying is spray drying or freeze drying.
[0013] According to another embodiment of the first aspect of the present application, in step one, a fluorine-containing polymer is applied to the surface of the silicon-based material by: mixing the fluorine-containing polymer with the silicon-based material solid, and grinding the solid mixture.
[0014] According to another embodiment of the first aspect of the present application, in step 2, sintering is performed at a temperature of 800-1100° C. for 10-36 hours, and the sintering is performed under an inert atmosphere.
[0015] According to another embodiment of the first aspect of the present application, the silicon-based material is pure silicon or a silicon material containing 0.5-50 wt% carbon. According to another embodiment of the first aspect of the present application, the silicon-based material is a powdered silicon-based material with a particle size of 50 nanometers to 15 microns.
[0016] The second aspect of the present application provides a modified silicon-based negative electrode material, which has an internal part and a surface part, wherein the internal part is pure silicon or a silicon material containing 0.5-50 weight % of carbon elements; the surface part covers at least a portion of the surface of the internal part, and the surface part is composed of a material containing carbon-fluorine bonds.
[0017] According to one embodiment of the second aspect of the present application, the modified silicon-based negative electrode material is prepared by the method of the present invention described above.
[0018] The third aspect of the present application provides a negative electrode, which is made using the modified silicon-based negative electrode material of the present application.
[0019] A fourth aspect of the present application provides a lithium-ion battery comprising the negative electrode of the present application.
[0020] In the specific implementation section below, the modified silicon-based negative electrode material of the present application and its preparation method and use are described in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a transmission electron microscope image of the modified silicon negative electrode material prepared in Example 1;
[0022] Figure 2 This is a silicon element mapping picture of the modified silicon negative electrode material prepared in Example 1;
[0023] Figure 3 This is a fluorine element mapping picture of the modified silicon negative electrode material prepared in Example 1. DETAILED DESCRIPTION
[0024] "Range" disclosed herein is in the form of lower limit and upper limit. It can be one or more lower limits, and one or more upper limits respectively. A given range is defined by selecting a lower limit and an upper limit. The selected lower limit and upper limit define the boundary of a particular range. All ranges that can be defined in this way are inclusive of end values and combinable, i.e. any lower limit can be combined with any upper limit to form a range. For example, a range of 60-120 and 80-110 is listed for a particular parameter, and it is understood that a range of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following ranges can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5.
[0025] In the present invention, unless otherwise specified, the numerical range "ab" represents an abbreviation of any real number combination between a and b, where a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" have been listed in this document, and "0-5" is just an abbreviation of these numerical combinations.
[0026] In the present invention, unless otherwise specified, all embodiments and preferred embodiments mentioned herein can be combined with each other to form a new technical solution.
[0027] In the present invention, unless otherwise specified, all technical features and preferred features mentioned herein can be combined with each other to form a new technical solution.
[0028] In the present invention, if there is no special explanation, the "including" mentioned herein means open or closed. For example, the "including" may mean that other components not listed may also be included, or only the listed components may be included.
[0029] In the present invention, when describing the spatial relationship of a specific component or object relative to other components or objects, the terms "inside", "outside", "above", "below", etc. are used to indicate that the former is located inside, outside, above or below the latter, and the two may be in direct contact, or be separated by a certain distance or separated by a third component or object.
[0030] The surface fluorine-modified silicon-based negative electrode material of the present invention can be prepared by a method comprising the following steps:
[0031] Step 1: applying a fluorine-containing polymer on the surface of the silicon-based material;
[0032] Step 2: Sintering the silicon-based material with the fluorine-containing polymer applied on the surface to obtain the surface fluorine-modified silicon-based negative electrode material.
[0033] The fluorinated polymer is used as a reaction precursor, and is applied to the surface of the silicon-based material as a raw material, and then sintered at high temperature, thereby preparing a fluorinated interface (a modified interface containing a carbon-fluorine bond) in situ. The surface fluorine-modified silicon-based negative electrode material is used to manufacture the negative electrode, and after being assembled into a lithium-ion battery, the modified negative electrode material will generate a high-density lithium fluoride interface layer (C-F+Li→C+LiF) in situ during the electrochemical cycle. The interface layer has the characteristics of high mechanical strength, high electronic insulation and high interface energy, which can effectively buffer the damage of the silicon-based negative electrode expansion stress and reduce the interface side reaction. Therefore, the use of the silicon-based negative electrode material with a fluorinated interface of the present invention can achieve the high cycle stability that the prior art has always sought but not achieved.
[0034] According to one embodiment of the present application, in the method of the present application, the silicon-based material to be modified as the raw material can be pure silicon, or a mixture or composite of silicon and carbon, such as a mixture or composite with a weight ratio of silicon to carbon of 50:50 to 99.5:0.5; preferably, the silicon-based material is pure silicon.
[0035] According to one embodiment of the present application, the silicon-based material is in the form of powder or small particles, and the particle size thereof is 50 nanometers to 15 micrometers.
[0036] According to one embodiment of the present application, the fluorine-containing polymer used for surface modification of silicon-based materials is a fluorine-containing C2-C6 olefin polymer, which is a partially fluorinated or fully fluorinated polymer, and may optionally contain one or more non-fluorine halogen atoms, such as chlorine, bromine or iodine, and may be a homopolymer or a copolymer. Preferably, the fluorine-containing polymer is selected from one or more of the following: polyvinylidene fluoride, polytetrafluoroethylene, polyvinylidene fluoride-hexafluoropropylene, polytrifluorochloroethylene, polyvinyl fluoride, ethylene-trifluorochloroethylene copolymer. More preferably, the fluorine-containing polymer is polytetrafluoroethylene.
[0037] According to one embodiment of the present application, the molecular weight of the fluorine-containing polymer is 15,000 to 2,000,000, preferably 100,000 to 1,500,000.
[0038] According to one embodiment of the present application, in the above step 1, the fluorine-containing polymer can be applied to the surface of the silicon-based material by a wet method or a dry method.
[0039] The wet method refers to mixing the silicon-based material and the fluorine-containing polymer in the presence of a solvent, wherein the solvent includes one or more of the following: water, C1-C6 alcohols, C2-C8 ethers, C6-C16 aliphatic hydrocarbons or aromatic hydrocarbons, C3-C8 ketones, C2-C12 esters, C3-C16 nitrogen-containing organic compounds, etc. According to a preferred embodiment, the solvent (also called dispersion medium or dispersant) in the wet method is N-methylpyrrolidone (NMP).
[0040] According to one embodiment of the present application, the fluorine-containing polymer, the silicon-based material and the organic solvent may be mixed together so that the fluorine-containing polymer and the silicon-based material are uniformly dispersed in the solvent. The dispersion system is hereinafter referred to as a "dispersion" or a "dispersion liquid", which may be in the form of a suspension.
[0041] According to one embodiment of the present application, in the dispersion, the mass ratio of the fluorine-containing polymer to the silicon-based material is 100:0.01 to 100:8, preferably 100:0.5 to 100:6, for example, 100:0.5, 100:1 or 100:6.
[0042] According to another embodiment of the present application, in the dispersion, the solvent is 50-200 ml, and the mass ratio of the solvent to the solid components (fluorine-containing polymer and silicon-based material) is 100:5 to 100:20.
[0043] Next, the suspension is dried to form a solid, preferably a powdered or granular solid. The drying can be performed by spray drying in a spray dryer or freeze drying in a freeze dryer; preferably, spray drying is used.
[0044] For the dry method, the silicon-based material and the fluorine-containing polymer are ground and mixed in a grinder (such as a ball mill) or a mortar without using a solvent, wherein the mass ratio of the silicon-based material to the fluorine-containing polymer is 100:0.01 to 100:8, preferably 100:0.5 to 100:6, for example, 100:0.5, 100:1 or 100:6.
[0045] According to one embodiment of the present application, the silicon-based material with a fluorine-containing polymer applied to the surface obtained in the above step is then sintered. According to another embodiment of the present application, the sintering is carried out at a temperature of 800-1100°C, preferably a sintering temperature of 850-950°C, more preferably 900°C. According to another embodiment of the present application, the duration of the sintering is 10-36 hours, preferably 12-30 hours, more preferably 15-30 hours. The sintering is carried out under an inert atmosphere, and the inert atmosphere is selected from one or more of the following: nitrogen, helium, neon, argon, preferably helium or argon.
[0046] After the above process steps, the obtained surface fluorine-modified silicon-based negative electrode material includes an inner part and a surface part, wherein the inner part is substantially pure silicon or a silicon material containing 0.5-50% by weight of carbon, and the outer part is a carbon-fluorine bond-containing substance formed after sintering the fluorine-containing substance. As described above, after the negative electrode is manufactured using the surface fluorine-modified silicon-based negative electrode material and assembled into a lithium-ion battery, the modified negative electrode material will generate a highly dense lithium fluoride interface layer in situ during the electrochemical cycle.
[0047] The surface-modified silicon-based negative electrode material of the present invention can be subsequently used to manufacture a negative electrode. According to an exemplary embodiment of the present application, the negative electrode is manufactured in the following manner: the surface-modified silicon-based negative electrode material is mixed with other materials (such as graphite, a binder, a solvent, etc.) to form a slurry, and then the slurry is applied to a substrate (such as a metal foil, preferably a copper foil), and then dried and heat-treated in sequence to obtain a negative electrode sheet.
[0048] The negative electrode can be assembled into a lithium ion battery together with a conventional positive electrode, electrolyte, separator, shell, etc. in the art.
[0049] The advantages of the present invention are:
[0050] 1. The silicon-based negative electrode material of the present application can effectively improve the interface stability of the silicon negative electrode and reduce the occurrence of interface side reactions by fluorine modification on the surface. The interface has high mechanical strength, good electronic insulation and high interface energy, which can greatly alleviate the volume expansion of the silicon-based negative electrode and significantly improve the capacity retention rate;
[0051] 2. The surface fluorine-modified silicon-based negative electrode material of the present invention can maintain negative electrode cycle stability for a long time. In contrast, the surface coating method reported in the prior art will deteriorate quickly during the charge-discharge cycle and does not have the long-term stability of the present invention;
[0052] 3. The technology of the present invention maintains high energy density while achieving interface stability, unlike the porous and nano-scale methods reported in the prior art, which reduce the key performance energy density in exchange for negative electrode interface stability.
[0053] 4. The technical process of the present invention is simple, the raw material source is wide and the cost is low, and it is easy to promote industrialization.
[0054] The method of the present application is specifically described in the following examples, the purpose of which is to provide a better understanding of the content of the present application. It should be understood that these examples are merely illustrative and not restrictive.
[0055] Example
[0056] The solvent used in the following examples is N-methylpyrrolidone (NMP), silicon powder was purchased from Liyang Tianmu Company with a particle size of 7.5 μm; polytetrafluoroethylene was purchased from Changshu San Ai Fu Zhenfu New Materials Co., Ltd. with a molecular weight of about 1.2 million; other reagents used were purchased from suppliers and used directly without further purification and treatment.
[0057] Example 1
[0058] 100 g of silicon powder, 1 g of polytetrafluoroethylene and 100 ml of NMP solvent were weighed and added into a beaker, and mixed at a rotation speed of 40 r / min for 4 hours to make the silicon powder and polytetrafluoroethylene uniformly mixed in the liquid phase.
[0059] The dispersion was spray dried using a spray dryer (inlet temperature 220°C, outlet temperature 100°C) to form solid particles. The solid particles were dried overnight in a vacuum oven at 100°C. They were then transferred to a muffle furnace, and the temperature of the muffle furnace was raised to 900°C at a rate of 5°C / min in an argon protective atmosphere, maintained at this temperature for 15 hours, and then naturally cooled to room temperature. A surface fluorinated silicon-based negative electrode material was obtained.
[0060] Figure 1 The transmission electron microscope image of the surface fluorinated silicon-based negative electrode material prepared in this example is shown. Figure 2 and Figure 3 The mapping diagrams of silicon and fluorine elements of the negative electrode material are shown respectively. It can be seen that the surface fluorinated silicon-based negative electrode material prepared in this embodiment is a fine and uniform powdered negative electrode material containing silicon and fluorine elements.
[0061] Example 2
[0062] 100 g of silicon powder, 0.1 g of polytetrafluoroethylene and 100 ml of NMP solvent were weighed and added into a beaker, and mixed at a rotation speed of 40 r / min for 4 hours to make the silicon powder and polytetrafluoroethylene uniformly mixed in the liquid phase.
[0063] The dispersion was spray dried using a spray dryer (inlet temperature 220°C, outlet temperature 100°C) to form solid particles. The solid particles were dried overnight in a vacuum oven at 100°C. They were then transferred to a muffle furnace, and the temperature of the muffle furnace was raised to 900°C at a rate of 5°C / min in an argon protective atmosphere, maintained at this temperature for 15 hours, and then naturally cooled to room temperature. A surface fluorinated silicon-based negative electrode material was obtained.
[0064] Example 3
[0065] 100 g of silicon powder, 6 g of polytetrafluoroethylene and 100 ml of NMP solvent were weighed and added into a beaker, and mixed at a rotation speed of 40 r / min for 4 hours to make the silicon powder and polytetrafluoroethylene uniformly mixed in the liquid phase.
[0066] The dispersion was spray dried using a spray dryer (inlet temperature 220°C, outlet temperature 100°C) to form solid particles. The solid particles were dried overnight in a vacuum oven at 100°C. They were then transferred to a muffle furnace, and the temperature of the muffle furnace was raised to 900°C at a rate of 5°C / min in an argon protective atmosphere, maintained at this temperature for 15 hours, and then naturally cooled to room temperature. A surface fluorinated silicon-based negative electrode material was obtained.
[0067] Example 4
[0068] 100 g of silicon powder, 1 g of polytetrafluoroethylene and 100 ml of NMP solvent were weighed and added into a beaker, and mixed at a rotation speed of 40 r / min for 4 hours to make the silicon powder and polytetrafluoroethylene uniformly mixed in the liquid phase.
[0069] The dispersion was spray dried using a spray dryer (inlet temperature 220°C, outlet temperature 100°C) to form solid particles. The solid particles were dried overnight in a vacuum oven at 100°C. They were then transferred to a muffle furnace, and the temperature of the muffle furnace was raised to 800°C at a rate of 5°C / min in an argon protective atmosphere, maintained at this temperature for 15 hours, and then naturally cooled to room temperature. A surface fluorinated silicon-based negative electrode material was obtained.
[0070] Example 5
[0071] 100 g of silicon powder, 1 g of polytetrafluoroethylene and 100 ml of NMP solvent were weighed and added into a beaker, and mixed at a rotation speed of 40 r / min for 4 hours to make the silicon powder and polytetrafluoroethylene uniformly mixed in the liquid phase.
[0072] The dispersion was spray dried using a spray dryer (inlet temperature 220°C, outlet temperature 100°C) to form solid particles. The solid particles were dried overnight in a vacuum oven at 100°C. They were then transferred to a muffle furnace, and the temperature of the muffle furnace was raised to 1000°C at a rate of 5°C / min in an argon protective atmosphere, maintained at this temperature for 15 hours, and then naturally cooled to room temperature. A surface fluorinated silicon-based negative electrode material was obtained.
[0073] Example 6
[0074] 100 g of silicon powder, 1 g of polytetrafluoroethylene and 100 ml of NMP solvent were weighed and added into a beaker, and mixed at a rotation speed of 40 r / min for 4 hours to make the silicon powder and polytetrafluoroethylene uniformly mixed in the liquid phase.
[0075] The dispersion was spray dried using a spray dryer (inlet temperature 220°C, outlet temperature 100°C) to form solid particles. The solid particles were dried overnight in a vacuum oven at 100°C. They were then transferred to a muffle furnace, and the temperature of the muffle furnace was raised to 1100°C at a rate of 5°C / min in an argon protective atmosphere, maintained at this temperature for 15 hours, and then naturally cooled to room temperature. A surface fluorinated silicon-based negative electrode material was obtained.
[0076] Comparative Example 1
[0077] In this comparative example, silicon powder was directly used as the negative electrode material.
[0078] Comparative Example 2
[0079] In this comparative example, a silicon-based negative electrode material with a surface carbon coating was prepared.
[0080] 100 g of silicon powder, 1 g of asphalt and 100 ml of NMP solvent were weighed and added into a beaker, and mixed at a rotation speed of 40 r / min for 4 hours to allow the silicon powder and asphalt to be uniformly mixed in the liquid phase.
[0081] The dispersion was spray dried using a spray dryer (inlet temperature 220°C, outlet temperature 100°C) to form solid particles. The solid particles were dried overnight in a vacuum oven at 100°C. They were then transferred to a muffle furnace, and the temperature of the muffle furnace was raised to 900°C at a rate of 5°C / min in an argon protective atmosphere, maintained at this temperature for 15 hours, and then naturally cooled to room temperature. A silicon-based negative electrode material with a surface carbon coating was obtained.
[0082] Performance Test Example
[0083] In this embodiment, the silicon-based negative electrode materials of the above embodiments 1-6 and comparative examples 1-2 are used to prepare negative electrode sheets according to the following steps.
[0084] 50 g of modified silicon-based negative electrode material, 950 g of graphite (purchased from Jiangxi Zichen Co., Ltd.), 30 g of PAA-Na binder (purchased from Blue Sea Black Stone Co., Ltd.), and 3 liters of deionized water were mixed and stirred thoroughly to form a slurry. The slurry was then heated to 6 g / cm 2 The copper foil coated with the slurry was then placed in a vacuum oven and dried overnight at 80°C in vacuum. After that, the electrode was compacted to a density of 1.65 g cm using a tablet press. -3 . Thus, the negative electrode sheet is obtained.
[0085] The above negative electrode plates were assembled with the lithium cobalt oxide positive electrode and PP separator into a 5Ah full battery, and the lithium battery electrolyte (LiPF6+ethylene carbonate (EC)+diethyl carbonate ethyl carbonate (DEC)) was filled into the battery. The battery was used to perform a cycle performance test at a charge and discharge rate of 1C, and the capacity retention rate and cell thickness expansion rate after 1000 cycles of charge-discharge cycles were recorded. The results are summarized in Table 1 below.
[0086] Table 1: Cyclic performance of silicon-based materials of Examples 1-6 and Comparative Examples 1-2
[0087]
[0088] From the experimental results in Table 1 above, it can be seen that the unmodified silicon-based negative electrode material of Comparative Example 1 and the carbon-layer-coated silicon-based negative electrode material of Comparative Example 2 both have very poor capacity retention after 1000 charge-discharge cycles, and both have significant cell expansion. However, after the introduction of the in-situ generated fluorinated interface layer protection, the capacity retention and thickness expansion of the silicon negative electrode material of the present application have been significantly improved. This shows that the high-quality lithium fluoride interface can effectively stabilize the silicon negative electrode interface and reduce the occurrence of side reactions, thereby greatly improving the cycle stability of the silicon-based negative electrode.
Claims
1. A method for preparing a surface fluorine-modified silicon-based negative electrode material, the method comprising the following steps: Step 1: applying a fluorine-containing polymer on the surface of the silicon-based material; Step 2: Sintering the silicon-based material with the fluorine-containing polymer applied on the surface to obtain the surface fluorine-modified silicon-based negative electrode material.
2. The method according to claim 1, characterized in that The fluorine-containing polymer is selected from one or more of the following: polyvinylidene fluoride, polytetrafluoroethylene, polyvinylidene fluoride-hexafluoropropylene, polychlorotrifluoroethylene, polyvinyl fluoride, ethylene-chlorotrifluoroethylene copolymer; The weight average molecular weight of the fluorine-containing polymer is 15,000 to 2,000,000.
3. The method according to claim 1, characterized in that In the step 1, the mass ratio of the silicon-based material to the fluorine-containing polymer is 100:0.5 to 100:
6.
4. The method according to claim 1, characterized in that In step 1, a fluorine-containing polymer is applied to the surface of the silicon-based material by a method selected from the following: Mixing a liquid dispersion of a fluorine-containing polymer with a silicon-based material, and then drying the mixture, wherein the drying is spray drying or freeze drying; preferably, the liquid dispersion contains a dispersion medium such as water, ethanol or N-methylpyrrolidone in addition to the fluorine-containing polymer; Alternatively, the fluoropolymer is mixed with the silicon-based material solid and the solid mixture is ground.
5. The method according to claim 1, characterized in that In step 2, sintering is performed at a temperature of 800-1100° C. for 10-36 hours, and the sintering is performed under an inert atmosphere.
6. The method according to claim 1, characterized in that The silicon-based material is pure silicon or a silicon material containing 0.5-50% by weight of carbon; The silicon-based material is a powdered silicon-based material with a particle size of 50 nanometers to 15 micrometers.
7. A modified silicon-based negative electrode material having an inner portion and a surface portion, wherein the inner portion is pure silicon or a silicon material containing 0.5-50 wt % of carbon element; The surface portion covers at least a portion of the surface of the inner portion, and the surface portion is composed of a material containing carbon-fluorine bonds.
8. The modified silicon-based negative electrode material according to claim 7, characterized in that: The modified silicon-based negative electrode material is prepared by the method described in claims 1-6.
9. A negative electrode, which is made using the modified silicon-based negative electrode material according to any one of claims 7 to 8. 10 . A lithium ion battery comprising the negative electrode according to claim 9 .
